Polyaniline nanosheet derived B/N co-doped carbon nanosheets as efficient metal-free catalysts for oxygen reduction reaction - Zhang, Yi; Zhuang, Xiaodong; Su, Yuezeng; Zhang, Fan; Feng, Xinliang (Journal of Materials Chemistry A, 2014)
A novel B/N co-doped porous carbon nanosheet with a high heteroatom doping content has been successfully prepared. Using amino-functionalized graphene oxide (GO) as the template, oxidation polymerization of aniline, 3-aminophenylboronic acid, and m-phenylenediamine generates GO-based polyaniline nanosheets functionalized with boronic acid (GO-CBP). After high-temperature treatment, graphene-based B/N co-doped carbon nanosheets (G-CBP) are obtained, which show a typical 2D morphology with a thickness of ∼20 nm. After CO 2 activation at 1000 °C, the obtained porous carbon nanosheets (G-CBP-a) have a thickness of ∼17 nm and a high specific surface area of 363 m2 g-1. Benefiting from its high surface area, unique 2D sheet nanostructure, and high heteroatom-doping contents (5.4% B and 5.3% N), G-CBP-a exhibits excellent electrochemical performance for the oxygen reduction reaction under alkaline conditions (0.1 M KOH), with a low half-wave potential (-0.27 V for G-CBP-a versus -0.18 V for Pt/C), a dominant four-electron transfer mechanism (n = 3.78 at -0.45 V), and excellent methanol tolerance and durability (10% current decrease after 20000 s operation), as well as a high diffusion-limiting current density (JL = -4.5 mA cm-2). This journal is © the Partner Organisations 2014.
CRIS-Team Scopus Importer:2023-03-20